PENDEKATAN PSIKOLOGI AGAMA DALAM PEMBELAJARAN AKIDAH AKHLAK DI MA AL-MUKHLISIN KAMPAO BLEGA BANGKALAN - Hayyul Mubarok (Risâlah, Jurnal Pendidikan dan Studi Islam, 2019)
The level of effectiveness of learning in MA AL-Mukhlisin Kampao, Blega District, Bangkalan District is strongly influenced by the behavior of educators and the behavior of students. Effective teaching behaviors include teaching clearly, using a variety of learning methods, using a variety of media or educational aids, enthusiasm, empowering students, and using contextual learning. Whereas student behavior can be viewed in terms of psychology. In the context, it relates to the scope of the learning approach used by the Akidah Akhlak teacher at MA Al-Mukhlisin, using the Psychology of Religion approach. His dentism, the approach of the psychology of religion can be defined as the study of human behavior or the study of the symptoms of the human soul associated with religion as a form of belief. Context as a reference to discuss these problems, using descriptive qualitative methods which are methods of analyzing the data obtained. The results of research conducted by researchers regarding the approach of the Psychology of Religion in the study of the Akidah Akhlak in MA Al-Mukhlisin, the researchers draw the following conclusions. In shaping the character of students in the learning process in terms of psychology by the teacher of the Akidah akhlak, traced the existence of inner pressures that befall on students who are very influential on achieving a goal of learning. Supporting Factors for the Implementation of the Psychological Approach Religion in Learning include; facilities and infrastructure, school culture, parental support, and individual differences.